Implementasi Nilai-Nilai Kesehatan dan Produktivitas pada Generasi Z melalui Edukasi Interaktif dan Pembinaan Karakter di SMK 02 PGRI Jatiroto - Karin Ardelia Araminta; Alfiyyah Alfiyyah; Hasna Nur Adilah; Tasman Tasman (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service research was motivated by the significant challenges faced by Generation Z in maintaining a balance between physical and mental health and productivity in the digital age. The increasing prevalence of mental health disorders and declining discipline among adolescents are important indicators of the need for character building integrated with health education. This study uses a descriptive qualitative approach to describe in depth the process of implementing health and productivity values through observation, interviews, and documentation of activities at school. The results show that interactive education approaches are effective in increasing students' awareness of healthy lifestyles, time management, and personal responsibility. Activities such as thematic education, congregational prayers, and reflective classes serve as a platform for building productive character that emphasizes balance between spiritual, social, and academic aspects. Students showed positive changes in behavior, such as increased regularity in studying, awareness of maintaining cleanliness, and the ability to manage stress and time more effectively. In conclusion, character building based on health and productivity values has a significant impact on shaping a resilient, disciplined, and competitive young generation, and can be used as a model for character education development in Indonesian vocational schools.